The tyrosine kinase inhibitor dasatinib reduces the growth of intracellular Mycobacterium tuberculosis despite impairing T-cell function - Wehrstedt, Stephanie; Kubis, Jan; Zimmermann, Andreas; Bruns, Heiko; Mayer, Daniel; Grieshober, Mark; Stenger, Steffen (European Journal of Immunology, 2018)
Tyrosine kinases are checkpoints for multiple cellular pathways and dysregulation induces malignancies, most notably chronic myeloid leukemia (CML). Inhibition of Abl-tyrosine kinases has evolved as a new concept for the treatment of CML and other malignant diseases. Due to the multiple immune-modulatory pathways controlled by tyrosine kinases, treatment with tyrosine kinase inhibitors (TKIs) will not only affect the biology of malignant cells but also modulate physiological immune functions. To understand the effects of TKIs on host defense against intracellular bacteria, we investigated the immunological impact of the dual Abl/Src TKI dasatinib on the cellular immune response to Mycobacterium tuberculosis (Mtb). Our results demonstrate that dasatinib impaired proliferation, cytokine release (IFN-γ, TNF-α, GM-CSF), expression of granulysin and degranulation of cytotoxic effector molecules of human Mtb-specific T-lymphocytes by inhibition of lymphocyte-specific protein tyrosine kinase (Lck) phosphorylation. Despite this profound inhibition of T-cell function, dasatinib suppressed growth of virulent Mtb in human macrophages co-cultured with autologous Mtb-specific T-cells (49±15%). Functional analysis suggested that growth inhibition is due to dasatinib-triggered lysosomal acidification in Mtb-infected macrophages. These results highlight the significance of innate immune responses, i.e. acidification of lysosomes, which control the multiplication of intracellular bacteria despite the lack of efficient T-cell support.
EVALuna2:35104